Interdyscyplinarny charakter nauczania języka niemieckiego a zdobycie kompetencji w drugim przedmiocie jako szansa dla nauczyciela języka obcego drugiego na rynku pracy - Niemiec-Knaś, Małgorzata (Neofilolog, 2019)
The current perspective of teaching German as a second or foreign language is very important in the context of teacher education reform. This article addresses the questions associated with the notion of interdisciplinarity in foreign language teaching and teacher education. The key question is how to prepare foreign language teachers for the difficult labor market. Two aspects are relevant to a future German teacher: one is professional knowledge on teaching German as a foreign language, the second is the knowledge and ability of teaching the second school subject.